Transforming borders functions in the Lithuanian‐polish‐Belarusian borderland - Nikiforova, Basia (Creativity Studies, 2010)
This article is an attempt to give an answer to the question: what are the consequences of the weakening factor of territorial belonging and how it in fact realizes in the Lithuanian‐Polish‐Belarusian borderland? In such a small territory as Lithuanian‐Polish‐Belarusian borderland it is possible to investigate two opposite, reciprocal processes: disappearances (the Lithuanian‐Polish borderland) and strengthening of borders (the Lithuanian‐Belarusian and Polish‐Belarusian borderland). Borders as markers of division have different functions. Using a “boundary narrative” we will analyse such functions as “border‐door”, “borderwall”, and “barrier”. A method of a free narration about a life on border will allow to create the generalized image of the inhabitant of a border zone, its way of life and to reveal its peculiar features. These peculiar features we will analyse in the case of Lithuanian‐Polish‐Belarusian borderland.Kintančių sienų funkcijos lietuvių, lenkų ir baltarusių paribyjeSantrauka. Straipsnyje bandoma atsakyti į klausimą – kokios yra teritorinės priklausomybės veiksnio silpnėjimo pasekmės ir kaip jis iš tikrųjų formuoja lietuvių, lenkų ir baltarusių paribį? Tokioje mažoje teritorijoje, kaip lietuvių, lenkų ir baltarusių paribys, galima ištirti du priešingus abipusius procesus: sienų nunykimą (lietuvių, lenkų ir baltarusių paribys) ir jų tvirtėjimą (lietuvių ir baltarusių bei lenkų ir baltarusių paribys). Sienos, kaip padalijimų žyminiai, atlieka skirtingas funkcijas. Vartojant ribos naratyvą, analizuojamos tokias funkcijas, kaip riba–durys, riba–siena ir barjeras. Laisvos naracijos apie gyvenimą pasienyje metodas leis sukurti apibendrintą gyvenimo būdo pasienyje vaizdą ir atskleisti savitus jo bruožus. Juos analizuosime lietuvių, lenkų ir baltarusių paribio atžvilgiu.Reikšminiai žodžiai: riba, paribys, kultūrinis paveikslas, ribų nunykimas ir stiprėjimas, socialiai atsakinga politika.First published online: 10 Feb 2011